Amygdala real‐time functional magnetic resonance imaging neurofeedback for major depressive disorder: A review. Issue 7 (21st May 2018) - Young, Kymberly D.; Zotev, Vadim; Phillips, Raquel; Misaki, Masaya; Drevets, Wayne C.; Bodurka, Jerzy
Abstract : Advances in imaging technologies have allowed for the analysis of functional magnetic resonance imaging data in real‐time (rtfMRI), leading to the development of neurofeedback (nf) training. This rtfMRI‐nf training utilizes functional magnetic resonance imaging (fMRI) tomographic localization capacity to allow a person to see and regulate the localized hemodynamic signal from his or her own brain. In this review, we summarize the results of several studies that have developed and applied neurofeedback training to healthy and depressed individuals with the amygdala as the neurofeedback target and the goal to increase the hemodynamic response during positive autobiographical memory recall. We review these studies and highlight some of the challenges and advances in developing an rtfMRI‐nf paradigm for broader use in psychiatric populations. The work described focuses on our line of research aiming to develop the rtfMRI‐nf into an intervention, and includes a discussion of the selection of a region of interest for feedback, selecting a control condition, behavioral and cognitive effects of training, and predicting which participants are most likely to respond well to training. While the results of these studies are encouraging and suggest the clinical potential of amygdala rtfMRI‐nf in alleviating symptoms of major depressive disorder, larger studies are warranted to confirm its efficacy.